Catering like a pro : from planning to profit - Halvorsen, Francine (New Jersey : John Wiley & Son, Inc., 2004)
"This complete, up-to-date guide to the art of catering presents all the proven business advice you need to put profits and success on your menu. It's packed with practical guidance on event planning, cooking, sanitation, and business practices, as well as wisdom - and recipes - from the biggest stars in catering."
1. The client-centered approach to catering -- 2. Defining and achieving your goals -- 3. Learning from the pros -- 4. Setting up your business -- 5. Managing an event from introduction to conclusion -- 6. The staff and subcontractors -- 7. Choosing a location -- 8. Nonfood supplies -- 9. Food safety and sanitation -- 10. Menus -- 11. Recipe file -- 12. Beverages.
Includes index.
Keywords: CATERERS AND CATERING -- HANDBOOKS, MANUALS, ETC